Svalbard as a Motif and a Place of Artistic Exploration: Insights from an Art Gallery Director - Berg, Jan Martin (Nordlit, 2020)
The article outlines the history of artists’ exploration of Svalbard as a motif, and then proceeds to describe a number of more recent art practices by the artists relating to Svalbard in the new millennium. The article traces the artists’ development from being supporters of research by providing visual material, to becoming researchers in their own right.